UNEARTHING CONNECTIONS: EXPLORING THE DIRECT IMPACT OF TILLAGE REQUIREMENTS ON CROP YIELD - Sadullaev, Azamat Nafiddinovich; Rajabov, Oxunjon Rauf oʻgʻli (Educational Research in Universal Sciences, 2024)
As agriculture faces evolving challenges in meeting the demands of a growing global population, understanding the intricate relationship between tillage practices and crop yield becomes paramount. This article delves into the direct effects of tillage requirements on crop productivity, scrutinizing how cultivation methods influence soil structure, nutrient availability, and water retention. Through an extensive review of empirical studies and field experiments, the article seeks to unravel the nuanced dynamics between tillage practices and yield outcomes. The findings shed light on the potential for optimizing tillage strategies to enhance agricultural sustainability, maximize resource efficiency, and mitigate the environmental impact of cultivation.